2016
DOI: 10.1016/j.ridd.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the supports intensity scale for children

Abstract: Support needs assessment instruments and recent research related to this construct have been more focused on adults with intellectual disability than on children. However, the design and implementation of Individualized Support Plans (ISP) must start at an early age. Currently, a project for the translation, adaptation and validation of the supports intensity scale for children (SIS-C) is being conducted in Spain. In this study, the internal structure of the scale was analyzed to shed light on the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
(46 reference statements)
1
16
0
3
Order By: Relevance
“…The scale used was the SIS-C ( Thompson et al 2016) adapted to Spanish (Verdugo et al 2016;Verdugo et al 2017). It aims to assess the extraordinary support that children or adolescents (aged 5 to 16 years) with ID, in comparison with their peers without disabilities, need to participate successfully in different activities of their daily lives.…”
Section: Instrumentmentioning
confidence: 99%
“…The scale used was the SIS-C ( Thompson et al 2016) adapted to Spanish (Verdugo et al 2016;Verdugo et al 2017). It aims to assess the extraordinary support that children or adolescents (aged 5 to 16 years) with ID, in comparison with their peers without disabilities, need to participate successfully in different activities of their daily lives.…”
Section: Instrumentmentioning
confidence: 99%
“…The results of a study by Verdugo et al (2016) on 814 subjects with intellectual and developmental disabilities in Spain showed that RMSEA indices with a value of 0.9, CFI with a value of approximately 0.99, and S-RMR with a value of 0.33 could support the hypothesis that the seven-factor model was the best and most suitable model for the SIS-A. In this seven-factor model, the factor load between the aspects and the total score of the SIS-A index was between 0.88 -0.98 which indicates a strong correlation between the aspects and the total score of SIS-A.…”
Section: Validitymentioning
confidence: 99%
“…This is perhaps most clearly articulated in the approach advocated by American Association on Intellectual and Developmental Disabilities (AAIDD), using tools, such as the Supports Intensity Scale (74, 75), that clearly are idiographically informed. Though more adult oriented, this approach has increasing relevance and is being investigated psychometrically among children and youth with disabilities (76). …”
Section: Theme 2: Disease and Disability Perspectives: Their Goodnessmentioning
confidence: 99%
“…The questions asked will inform the choice of the tools to find answers. Other contemporary measurement tools designed to capture functional information, either in relation to ICF domains (101) or in terms of needed functional supports (74, 75), are presently available primarily for adults but are likely to prove useful as part of implementation of the disability perspective in child health with further validation in this population (76). …”
Section: Theme 4: Moving Forward: a Progressive Agenda For Deploying mentioning
confidence: 99%
See 1 more Smart Citation